2020
DOI: 10.1111/emre.12413
|View full text |Cite
|
Sign up to set email alerts
|

Exclusive Talent Management: Unveiling the Mechanisms of the Construction of an Elite Community

Abstract: This paper aims at contributing to the talent management (TM) and organisation research fields by investigating the mechanisms of elite construction through an exclusive TM programme in a multinational company (MNC). We conducted an exploratory single-case study in an MNC operating in more than 15 countries, by interviewing HR managers as representatives of top management and participants in a TM programme in seven countries. Other data sources included non-participant observation and the use of internal and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 128 publications
(226 reference statements)
1
15
0
Order By: Relevance
“…In particular, the work focuses on inclusive talent management (Al Ariss et al, 2014), which takes into account all or the majority of employees, and regards talents as strengths (Swailes, Downs & Orr, 2014). In doing so, it offers a more independent view of talent status (Bonneton et al, 2020;De Boeck et al, 2018;, which describes whether an individual is formally identified as talent or not by an organization (De Boeck et al, 2018).…”
Section: Rationale For the Researchmentioning
confidence: 99%
See 4 more Smart Citations
“…In particular, the work focuses on inclusive talent management (Al Ariss et al, 2014), which takes into account all or the majority of employees, and regards talents as strengths (Swailes, Downs & Orr, 2014). In doing so, it offers a more independent view of talent status (Bonneton et al, 2020;De Boeck et al, 2018;, which describes whether an individual is formally identified as talent or not by an organization (De Boeck et al, 2018).…”
Section: Rationale For the Researchmentioning
confidence: 99%
“…Exclusive talent management is the dominating paradigm in the research area (Bonneton, Festing, Muratbekova-Touron, 2020) and especially focuses on talent practices of talent identification, talent development and employee retention of one to ten percent of employees (Swailes, Downs, & Orr, 2014). The degree of workforce segmentation describes the extent to which resources, for example training budget, are distributed unequally among employees.…”
Section: Talent Management Philosophy and Tensionsmentioning
confidence: 99%
See 3 more Smart Citations